Synthesis and structure elucidation of some new hydrazones and oxadiazolines: Anticonvulsant activities of 2-(3-acetyloxy-2-naphthyl)-4-acetyl-5-substituted-l,3,4-oxadiazolines - (:unkn) unknown (My University, 1998)
We have synthesized new compounds, which have the structures of 3-hydroxy-2-naphthoic acid (substitutedmethylene)-hydrazides and 2-(3-acetyloxy-2-naphthyl)-4-acetyl-5-substituted-1,3,4-oxadiazolines to establish their anticonvulsant activities. Twelve compounds were original. Hydrazones were obtained by condensation of 3-hydroxy-2-naphthoic acid hydrazide with appropriate aldehydes. Cyclization of the hydrazones in the presence of acetic anhydride gave oxadiazolines. The structures of these substances were confirmed their sharp melting points, elementary analysis, UV, 'H-NMR and mass spectral methods. When evaluated for anticonvulsant activities in mice, the protection afforded by oxadiozolines against pentylenetetrazole-induced convulsions ranged from 0 to 60%. © 1998 Lippincott Williams & Wilkins.
Keywords: 1,3,4-oxadiazolines; Anticonvulsant; Hydrazones